2022
DOI: 10.14309/ajg.0000000000001777
|View full text |Cite
|
Sign up to set email alerts
|

Disease Burden and Unmet Need in Eosinophilic Esophagitis

Abstract: Eosinophilic esophagitis (EoE) is a chronic, progressive, type 2 inflammatory disease of increasing prevalence, characterized by symptoms of dysphagia and reduced quality of life. A dysregulated type 2 immune response to food and aeroallergen leads to barrier dysfunction, chronic esophageal inflammation, remodeling, and fibrosis. Patients with EoE have impaired quality of life because of dysphagia and other symptoms. They may also suffer social and psychological implications of food-related illness and expensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 108 publications
0
24
0
Order By: Relevance
“…In the United Kingdom, although the prevalence of severe, uncontrolled eosinophilic asthma is low (1%), the associated health-related costs are four times greater (cost ratio 3.9 (95% IC 3.7-4.1)) [16]. Moreover, healthcare resource utilization may be particularly high in EGID, with contributing factors including diagnostic delays (poor disease recognition), repeated endoscopy, and lack of approved medications [11,17,18]. Te median total annual cost of a single eosinophilic esophagitis case in the United States was estimated at USD $3,300 (outpatient visits, pharmacy, and endoscopy); the total health utilization costs per year vary between $350 and 950 million [19][20][21][22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the United Kingdom, although the prevalence of severe, uncontrolled eosinophilic asthma is low (1%), the associated health-related costs are four times greater (cost ratio 3.9 (95% IC 3.7-4.1)) [16]. Moreover, healthcare resource utilization may be particularly high in EGID, with contributing factors including diagnostic delays (poor disease recognition), repeated endoscopy, and lack of approved medications [11,17,18]. Te median total annual cost of a single eosinophilic esophagitis case in the United States was estimated at USD $3,300 (outpatient visits, pharmacy, and endoscopy); the total health utilization costs per year vary between $350 and 950 million [19][20][21][22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are some patients who may respond to treatment with endoscopic dilation, which will reduce the risk of future food impaction, but there is no associated benefit in terms of improving histological eosinophilia (10). Whenever possible, treatment should be oriented by a multidisciplinary team, consisting of a gastroenterologist, immunoallergologist and nutritionist for assessment of diet feasibility and nutritional follow-up (12,13).…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 99%
“…Severe clinical disease was defined based on our clinical practice as presence of symptoms with a significant impact on quality of life and/or ≥ 1 visit to the Emergency Department and/or hospitalization due to EoE complications, namely severe dysphagia, food impaction and/or esophageal perforation due to the progression of esophageal stricture. In the present study, the burden of disease on quality of life was subjectively assessed as reported by the patient and/or families in 3 domains, including emotional distress, limited normal feeding and restricted social activities, as the scores currently available for this assessment are not validated for Portuguese (9,10). The criteria for defining EoE complications were adapted from Furuta GT et al (18) and Gomez Torrijos E et al (19).…”
Section: Clinical Analysismentioning
confidence: 99%
See 2 more Smart Citations